PENGARUH PEMBERIAN PISANG AMBON TERHADAP PENURUNAN TEKANAN DARAH PRA LANSIA HIPERTENSI DI WILAYAH KERJA PUSKESMAS NILAM SARI - Liffia Oka Lydia; Neila Sulung; Adriani Adriani (LPPM Universitas Abdurrab, 2022)
Based on the health profile of Sumatra Barat Province, the prevalence of hypertension sufferers in Sumatra Barat was almost close to the national figure. This indicates that hypertension in Sumatra Barat needs serious attention. Continuous treatment can be done by applying the DASH diet (Dietary Approach to Stop Hypertension) by consuming potassium-rich foods like banana. Therefore, a study was conducted to determine the effect of giving Cavendish banana to decrease blood pressure in pre-hypertensive elderly in the working area of ​​Puskesmas Nilam Sari. The study population was 38 pre-elderly people (45-59 years) using a purposive sampling technique as many as 20 pre-elderly people who met the inclusion criteria. The results showed that the average systolic value before giving Cavendish banana was 148.75 mmHg and the diastolic was 85.55 mmHg. The mean systolic value after giving Cavendish banana was 132.25 mmHg with the diastolic value was 72.25 mmHg. The p-value (0.0001<0.05) means that there was a significant effect on diastolic blood pressure in pre-elderly between before and after giving Cavendish banana. It can be concluded that the Cavendish banana can be used as an alternative diet for reducing blood pressure in pre-aged hypertension non-pharmacologically.